2011
DOI: 10.1007/s00520-011-1134-8
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture improves health-related quality-of-life (HRQoL) and sleep in women with breast cancer and hot flushes

Abstract: Both EA and HT increased HRQoL and sleep, probably through decreasing numbers of and distress by hot flushes. Although flushes decreased less in the EA group than in the HT group, HRQoL improved at least to the same extent maybe due to other effects of EA, not induced by HT, e.g. on anxiety, vitality and sleep, supported by subscale analyses. EA should be further evaluated as treatment for women with breast cancer and climacteric complaints, since HT no longer can be recommended for these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
91
0
16

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 45 publications
1
91
0
16
Order By: Relevance
“…Contradictory results have been published by randomized controlled trials (RCTs) on the effects of acupuncture on alleviating menopause-related sleep disturbances. [6][7][8][9][10] Furthermore, considering that sleep disturbances are strongly associated with the levels of sex hormone levels, researchers have studied the response of sex hormones to acupuncture in women experiencing menopause-related symptoms and have published conflicting results. [11][12][13] However, the effect of acupuncture on menopause-related sleep disturbances and whether the effectiveness of acupuncture in managing menopause-related sleep disturbances is affected by acupuncture-induced changes in sex hormones levels remain unclear.…”
mentioning
confidence: 99%
“…Contradictory results have been published by randomized controlled trials (RCTs) on the effects of acupuncture on alleviating menopause-related sleep disturbances. [6][7][8][9][10] Furthermore, considering that sleep disturbances are strongly associated with the levels of sex hormone levels, researchers have studied the response of sex hormones to acupuncture in women experiencing menopause-related symptoms and have published conflicting results. [11][12][13] However, the effect of acupuncture on menopause-related sleep disturbances and whether the effectiveness of acupuncture in managing menopause-related sleep disturbances is affected by acupuncture-induced changes in sex hormones levels remain unclear.…”
mentioning
confidence: 99%
“…In the study by Frisk et al, 17 sleep improvements appeared largely related to reduction in hot flash symptoms. As a result, it is unclear from the study by Frisk et al 17 whether acupuncture had a direct impact on sleep disturbance. Of note, Feng et al 16 was the only study evaluating sleep to use a Chinese medicine differential diagnosis (phlegm stasis binding) as diagnostic criteria.…”
Section: Sleep Disturbancementioning
confidence: 90%
“…In this study, 10 women with breast cancer who were experiencing sleep disturbance and hot flashes received 3 acupuncture sessions in a single arm design. Otte Frisk et al 17 conducted this study when hormone therapy was still an acceptable treatment for this population, which it is no longer. 6 Sleep parameters improved significantly in both studies, with acupuncture superior to fluoxetine and equivalent to hormone therapy.…”
Section: Sleep Disturbancementioning
confidence: 99%
“…20,22,24 Several recent trials have shown that acupuncture, a therapy originating from Traditional Chinese Medicine, is an effective treatment for hot flashes in breast cancer survivors with few, if any, side effects. 2529 Compared to sham-acupuncture and no treatment control groups, acupuncture demonstrated a clear improvement in hot flash frequency in a double blind randomized controlled trial of 94 women post-treatment for breast cancer. 30 Acupuncture has also been shown to be more effective than self-care alone for reducing hot flash frequency and intensity, an effect that was maintained at the 12 month follow-up assessment.…”
Section: Introductionmentioning
confidence: 99%
“…33 Several of the above trials also reported improved sleep as a secondary outcome. 25,26,30,31 However, rigorously conducted trials with larger sample sizes and the inclusion of active comparison interventions are required before making definitive statements about the efficacy of acupuncture in improving sleep disturbance related to hot flashes.…”
Section: Introductionmentioning
confidence: 99%